Disability Transfers, Self-Reported Health, and the Labor Force Attachment of Older Men: Evidence from the Historical Record - Bound, J.; Waidmann, T. (Quarterly Journal of Economics, 1992)
We use trends in self-reported disability to gauge the impact of the growth of disability transfer programs on the labor force attachment of older working-aged men. Our tabulations suggest that between 1949 and 1987, about half of the 4.9 percentage point drop in the labor force participation of men aged 45–54 and between one quarter and one third of the 19.9 point drop among men aged 55–64 represented a movement of men out of the labor force and onto the rolls of transfer programs targeted at the disabled. Since the expansion of transfer programs represents only one of the forces behind this movement, these figures represent upper bounds on the impact of such programs on work force attachment.